Pengaruh Motivasi Belajar, Dukungan Keluarga dan Campus Visit terhadap Keputusan Melanjutkan Studi ke Perguruan Tinggi pada Siswa Kelas XII SMA Negeri Jakarta Utara Tahun Ajaran 2025/2026 - Indah Lestari; Herlitah Herlitah; Saparuddin Saparuddin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of learning motivation, family support, and campus visit on the decision to continue studies to higher education among twelfth-grade students of public senior high schools in North Jakarta in the academic year 2025/2026. The transition from secondary to higher education is a critical stage for students, yet many students face uncertainty in determining their educational future. This research employs a quantitative approach with an explanatory correlational design. Data were collected through a survey using questionnaires distributed to 220 respondents selected through multistage sampling techniques, including purposive sampling and proportionate stratified random sampling. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results indicate that learning motivation has a positive and significant effect on the decision to continue studies to higher education, while campus visit also has a positive and significant effect. However, family support has a positive but not significant effect on the decision to continue studies. The coefficient of determination (R²) of 0.593 indicates that 59.3% of the variation in the decision to continue studies can be explained by the three independent variables, while the remaining 40.7% is explained by other variables outside the research model. These findings provide important implications for schools, particularly in strengthening career guidance and counseling services, as well as facilitating campus visit activities to assist students in making more informed and well-planned decisions about their higher education choices.